Micro/nanorobots for remediation of water resources and aquatic life - Wang, Haocheng; Jing, Yizhan; Yu, Jiuzheng; Ma, Bo; Sui, Mingyang; Zhu, Yanhe; Dai, Lizhou; Yu, Shimin; Li, Mu; Wang, Lin (Frontiers in Bioengineering and Biotechnology, 2023)
Nowadays, global water scarcity is becoming a pressing issue, and the discharge of various pollutants leads to the biological pollution of water bodies, which further leads to the poisoning of living organisms. Consequently, traditional water treatment methods are proving inadequate in addressing the growing demands of various industries. As an effective and eco-friendly water treatment method, micro/nanorobots is making significant advancements. Based on researches conducted between 2019 and 2023 in the field of water pollution using micro/nanorobots, this paper comprehensively reviews the development of micro/nanorobots in water pollution control from multiple perspectives, including propulsion methods, decontamination mechanisms, experimental techniques, and water monitoring. Furthermore, this paper highlights current challenges and provides insights into the future development of the industry, providing guidance on biological water pollution control.